Equitable investment in the veterinary workforce is foundational to One Health and planetary wellbeing - Hassan, Latiffah; Alders, Robyn; Cleveland, Sarah; Pfeiffer, Dirk; Walzer, Chris; Vora, Neil M.; Plowright, Raina K. (Elsevier, 2025)
undefined